Pathogenic synergy: dysfunctional mitochondria and neuroinflammation in neurodegenerative diseases associated with aging - Mani, Shalini; Wasnik, Samiksha; Shandilya, Chesta; Srivastava, Vidushi; Khan, Saboor; Singh, Keshav K. (Frontiers in Aging, 2025)
The term “neurodegenerative diseases” (NDDs) refers to a range of aging-associated conditions, including Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis. Unique clinical symptoms and underlying pathological mechanisms distinguish each of these illnesses. Although these conditions vary, they share chronic neuroinflammation as a defining characteristic. Protein aggregation and mitochondrial dysfunction are believed to play a role in initiating the neuroinflammatory response and, subsequently, the development and course of these illnesses. Apart from providing energy to the cells, mitochondria are involved in the immunoinflammatory response associated with neurological disorders such as Alzheimer’s disease, Parkinson’s disease, multiple sclerosis, and epilepsy. This involvement is attributed to controlling processes such as inflammasome activation and cell death. Under inflammatory conditions, the underlying regulatory mechanisms for these aging-associated disorders may include calcium homeostasis imbalance, mitochondrial oxidative stress, mitochondrial dynamics, and epigenetics. Various NDDs are linked to neuroinflammation and mitochondrial dysfunction. The linkages between these occurrences are becoming more apparent, but the etiology of these pathologic lesions is yet to be elucidated. This review examines the role of neuroinflammation and mitochondrial dysfunction in the growth and course of NDDs, emphasizing the possibility of identifying novel therapeutic targets to address aging-related neurodegenerative processes and retard the progression of these illnesses.